2018
DOI: 10.2147/nss.s163071
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping hours: what is the ideal number and how does age impact this?

Abstract: The objective of this narrative review paper is to discuss about sleep duration needed across the lifespan. Sleep duration varies widely across the lifespan and shows an inverse relationship with age. Sleep duration recommendations issued by public health authorities are important for surveillance and help to inform the population of interventions, policies, and healthy sleep behaviors. However, the ideal amount of sleep required each night can vary between different individuals due to genetic factors and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
166
1
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(202 citation statements)
references
References 79 publications
13
166
1
22
Order By: Relevance
“…Sleep quality was strongly correlated with better psychological outcomes, including lower depression and fatigue, and higher vigor, indicating that sleep quality led to a global improvement in mood, similarly to what has been unanimously observed (49,55,(57)(58)(59). We speculate that sleep duration was not demonstrated to a major factor of mood states or any other characteristic in athletes because in higher quality sleep duration tends to play a less important role (60,61).…”
Section: Linear Correlationssupporting
confidence: 63%
“…Sleep quality was strongly correlated with better psychological outcomes, including lower depression and fatigue, and higher vigor, indicating that sleep quality led to a global improvement in mood, similarly to what has been unanimously observed (49,55,(57)(58)(59). We speculate that sleep duration was not demonstrated to a major factor of mood states or any other characteristic in athletes because in higher quality sleep duration tends to play a less important role (60,61).…”
Section: Linear Correlationssupporting
confidence: 63%
“…In a systematic review, longer sleep duration has been found to be related with better emotional regulation and quality of life in 5-17-year-old children [26]. The overall sleep duration for the children in the present study was 9-11 hours per night, which is in line with general sleep duration recommendations [2,27], but contrasts with other studies describing less sleep duration in the latest decennium [7,28]. Longer sleep duration was seen in younger children compared to older.…”
Section: Discussionsupporting
confidence: 85%
“…In 2017, the NSF published evidence-based recommendations and guidance to the public regarding indicators of good sleep quality for children under 5 years of age [14], which are summarized in Table 1. Nevertheless, it is worth noting that even though the normative sleep duration values are helpful and inform what constitutes the norm and what is considered outside the norm for a given age, these references provide norms at the population level standpoint and need to be individualized for each patient in the clinical setting [15].…”
Section: The Development Of a Healthy Sleep Rhythm In Early Childhoodmentioning
confidence: 99%